Diagnosis and Management of Aortic Valvular Disease in the Elderly - Gorton, Andrew J.; Keshavamurthy, Suresh; Saha, Sibu P. (International Journal of Angiology, 2022)
Aortic valvular disease, including aortic stenosis and aortic regurgitation, is increasingly common with age. Due to the aging population, more elderly patients are presenting with aortic valve pathology and expectations for prompt diagnosis and efficacious treatment. The current paradigm for aortic valve disease is based on surgical or interventional therapy. In this review, we discuss the approach to diagnosing aortic valvular disease and the different options for treatment based on the most recent evidence.
Keywords: aortic valve disease; aortic dilation; cardiac biomarkers; cardiac surgery; cardiovascular surgical disease; diagnostic procedure; valvuloplasty